Levels of Ischemia-Modified Albumin in Transient Tachypnea of the Newborn - Oztekın, Osman; Kalay, Salih; Tayman, Cuneyt; Namuslu, Mehmet; Celık, Hüseyin Tugrul (American Journal of Perinatology, 2015)
Aim The aim of the article is to evaluate ischemia-modified albumin (IMA) levels in infants with transient tachypnea of the newborn (TTN) and to find out its relation to the disease severity.Patients and Methods Infants with > 37 weeks of gestation, without any respiratory and cardiac symptoms and without any maternal health problems, and diagnosed as TTN were allocated as the study group. Patients with obvious retractions, grunting, hypercarbia (Pco2 > 60 mm Hg) or hypoxia (oxygen saturation < 88% with Fio2 of 0.60) were managed with nasal continuous positive airway pressure (CPAP). During the postnatal 0 to 24 hours, blood samples were collected in 2 mL for IMA.Results A total of 47 patients were diagnosed TTN, and allocated as the study group. Of the 47 patients, 43 patients without respiratory symptoms were enrolled as the control group. IMA levels in TTN were found to be significantly higher (p < 0.05). In addition, IMA levels were significantly increased in the nasal CPAP group versus supplemental oxygen therapy groups (p < 0.05). IMA levels were determined to be significantly higher in the > 3 days of oxygen therapy group (p < 0.05). IMA levels with a cutoff point of 0.87 ABSU, sensitivity of 81.1% and specificity of 69.8% predicted TTN (area under the curve [AUC] = 0.85; p < 0.05). IMA levels with > 0.98 ABSU, 78% sensitivity, and 86% specificity indicated the prediction of CPAP requirement (AUC = 0.86; p < 0.05).Conclusion IMA levels were significantly higher in infants with diagnosed TTN. Therefore, IMA may be used as a new marker for predicting TTN and disease severity.
Keywords: transient tachypnea of the newborn; ischemia-modified albumin; newborn